The Correlational Study Between Personality, Learning Style and Vocabulary English Achievement of Students Grade Eight SMPN 25 Makassar - Sitti Harfiana; Haryanto Atmowardoyo; Kisman Salija (Har Press Indonesia, 2022)
This research is aimed at finding out the correlation between students’ personality, learning style and vocabulary English achievement of the students grade eight SMPN 25 Makassar. This study applied correlation research design. The researchers used personality questionnaire from Taruna Psychology to investigate the student’s personality traits, learning style questionnaire by Barsch to investigate students’ learning style and vocabulary test to measure the vocabulary achievement of the students. The population of this research was all of students grade eight SMP 25 Makassar, and involving sample of one class that selected randomly consist of 30 students. After analyzing X1 Variable (Students’ Personality), X2 (Students’ Learning Style) and Y Variable (Students’ Vocabulary Achievement) the result of this research showed that most of the students was extrovert person, most of them also prefer auditory learning style, and most of students have very poor vocabulary achievement. The result of the questionnaire and test was analyzed by multiple regression analysis in SPSS 22.00. It was found that there was no correlation between personality and vocabulary achievement, also the correlation between students’ learning style and vocabulary achievement also showed that there was no correlation, and the correlation among personality, learning style and vocabulary achievement also found that there was no correlation.